"I Didn't Want My Baby to Pass, But I Didn't Want Him Suffering Either": Comparing Bereaved Parents' Narratives With Nursing End-of-Life Assessments in the Pediatric Intensive Care Unit. Issue 5 (6th October 2022) - Broden, Elizabeth G.; Hinds, Pamela S.; Werner-Lin, Allison V.; Curley, Martha A. Q.; ,
Abstract : Little is known about how nursing care at the end of a child's life impacts long-term parental bereavement. We aimed to explain, contextualize, and examine comparisons between quantitative trends in children's end-of-life care and parents' qualitative perceptions. We used a mixed methods design, combining quantitative data from the RESTORE clinical trial with qualitative interviews with bereaved parents. Patients who died during RESTORE were included in quantitative analyses. A subset of their parents was interviewed 7 to 11 years later. The quantitative analyses included 104 children. Eight parents were interviewed; 4 had a child die after cancer, and 4 had a child die after a complex chronic illness. Quantitatively, patients' pain and sedation scores were generally comfortable. Children died with multiple invasive devices in place. Parents' descriptions of their child's comfort and critical care requirements differed by illness trajectory (cancer, complex chronic illness). Parents' memories of their child's suffering aligned with peaks in clinical scores, rather than averages. Invasive devices and equipment altered parents' ability to make meaningful final memories with the dying child. Pediatric intensive care clinicians may need to broaden how they attend to dying children's pain and corresponding parental distress, as parents' memories of their dying child's suffering persist for years.